Using near infrared spectroscopy to assess the composition of New Zealand aquaculture species. Issue 5 (August 2018) - Miller, Matthew R; Puddick, Jonathan; Symonds, Jane E; Walker, Seumas P; Tian, Hong (Sabrina)
Near infrared spectroscopy has been employed to determine the proximate composition of Chinook salmon ( Oncorhynchus tshawytscha ) and Greenshell Mussels™ ( Perna canaliculus ). This work was presented at the Australian Near Infrared Spectroscopy Group and New Zealand Near Infrared Spectroscopy Society meeting in Rotorua, 11–12 April 2018, where it won the best overall presentation award for Near Infrared Science (Figure 1).